2004
DOI: 10.1177/107327480401100606
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Black Men, and Prostate Cancer: What is Reality?

Abstract: Lack of discussion about the decision to screen for prostate cancer and general lack of culturally appropriate communication with healthcare providers has engendered distrust, created fear, fostered disconnect, and increased the likelihood of nonparticipation in prostate cancer screening among black men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 16 publications
7
80
0
3
Order By: Relevance
“…The men in the current study were willing to share the experiences they had with prostate cancer, although other studies have found that cancer is not talked about openly among African Americans because of its associated stigma (Gray, Fitch, Phillips, Labrecque, & Fergus, 2000;Woods, Montgomery, Belliard, Ramirez-Johnson, & Wilson, 2004;Woods, Montgomery, & Herring, 2004). The lack of suspicion and distrust of physicians and other healthcare providers was the most important finding in the present investigation.…”
Section: Discussionmentioning
confidence: 49%
“…The men in the current study were willing to share the experiences they had with prostate cancer, although other studies have found that cancer is not talked about openly among African Americans because of its associated stigma (Gray, Fitch, Phillips, Labrecque, & Fergus, 2000;Woods, Montgomery, Belliard, Ramirez-Johnson, & Wilson, 2004;Woods, Montgomery, & Herring, 2004). The lack of suspicion and distrust of physicians and other healthcare providers was the most important finding in the present investigation.…”
Section: Discussionmentioning
confidence: 49%
“…The first was that racial differences cannot be determined with samples based on one racial group. e.g., 811 Some studies reported that many African-American men lack knowledge about the prostate 9,11 and medical recommendations about prostate cancer screening 8, 10, 11. One study found that despite African-American’s low levels of knowledge regarding the PSA and the DRE, those who were unscreened had even less knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mortality rate of cancer is 37% higher among African American males than it is for White males (Jemal et al, 2008). Further, African American males have the highest incidence and mortality rates of prostate cancer in the world and die from the disease at a rate 2.3 times that of White men (Woods, Montgomery, Belliard, Johnson, & Wilson, 2004).…”
mentioning
confidence: 99%